Assessing the Value of Grazed Corn Residue for Crop and Cattle Producers. Issue 1 (1st February 2019) - Redfearn, Daren; Parsons, Jay; Drewnoski, Mary; Schmer, Marty; Mitchell, Rob; MacDonald, James; Farney, Jaymelynn; Smart, Alexander
Abstract : Core Ideas: Grazed corn residue is a cost‐efficient forage resource. Current value of grazed corn residue is $95 M returned to the crop sector in NE, SD, KS, and ND. Gross value for grazed corn residue is $191 M for the beef cattle sector in NE, SD, KS, and ND. Opportunities exist to increase use of corn residue grazing. Transportation costs and animal care arrangements are complicating factors. Integrated crop–livestock systems have included grazing perennial grasses during the spring and summer and corn ( Zea mays L.) residues during the winter. Our objectives were to identify opportunities for expanded corn residue use through grazing and provide an economic assessment for value‐added grazing. We estimated the economic value to the crop sector through grazing leased corn residue at over $95 million for Nebraska, South Dakota, Kansas, and North Dakota under current management. Additionally, gross economic value to the livestock sector in these states was estimated at greater than $191 million. Advantages for increased grazing use of corn residue include managing residue quantity in high‐yielding environments, providing a source of supplemental revenue, and expanding integrated crop–livestock systems using a simple, but cost‐efficient practice.